Clade 2.3.4.4b but not historical clade 1 HA replicating RNA vaccine protects against bovine H5N1 challenge in mice - David W. Hawman; Thomas Tipih; Eddie Hodge; E. Taylor Stone; Nikole Warner; Natalie McCarthy; Brian Granger; Kimberly Meade-White; Shanna Leventhal; Kiara Hatzakis; Stephanie Park; Karen Gaffney; et al. (Nature Communications)
Abstract The ongoing circulation of influenza A H5N1 in the United States has raised concerns of a pandemic caused by highly pathogenic avian influenza. Although the United States has stockpiled and is prepared to produce millions of vaccine doses to address an H5N1 pandemic, currently circulating H5N1 viruses contain multiple mutations within the immunodominant head domain of hemagglutinin (HA) compared to the antigens used in stockpiled vaccines. It is unclear if these stockpiled vaccines will need to be updated to match the contemporary H5N1 strains. Here we show that a replicating RNA vaccine expressing the HA of an H5N1 isolated from a US dairy cow confers complete protection against homologous lethal challenge in mice. A repRNA encoding the HA of a clade 1 H5 from 2004 (A/Vietnam/1203/2004) as utilized by some stockpiled vaccines, confers only partial protection. Our data highlight the utility of nucleic acid vaccines to be rapidly updated to match emergent viruses of concern while demonstrating that contemporary bovine H5N1 viruses can evade immunity elicited by historical HA antigens.